Fostering Ubuntu in Teacher Education for South African Higher Education - Mncedisi Christian Maphalala; Ntombikayise Nkosi (Journal of Education and Learning Technology)
Ubuntu is a foundational philosophy rooted in South African culture that emphasises the importance of interconnectedness, community well-being, and our shared humanity. Its relevance in education, particularly teacher training, is increasingly recognised as essential to foster inclusive and socially responsible learning environments. This study explores the integration of Ubuntu principles into teacher education programs at institutions of higher learning in South Africa and proposes strategies for embedding Ubuntu into teacher training, thereby enhancing both the teaching approach and the societal impact on future educators. For this study, a systematic literature review (SLR) was adopted to consolidate existing research on Ubuntu in education for this study. The review follows the PRISMA guidelines and includes empirical studies published between 2014 and 2024. The literature search focused on prominent academic databases such as Scopus, Web of Science, ERIC, and Google Scholar, concentrating on peer-reviewed articles on Ubuntu, teacher education, and cultural pedagogy. The review identified 18 studies that met the inclusion criteria, revealing significant themes regarding applying Ubuntu in educational settings. These studies highlighted the necessity of curriculum integration, which involves incorporating Ubuntu principles into the design and delivery of the curriculum, inclusive teaching methods, experiential learning, community involvement, and advocacy for policy changes as critical strategies for incorporating Ubuntu principles into teacher education.